Duration of Diabetes and Pancreatic Cancer in a Case-Control Study in the Midwest and the Iowa Women’s Health Study (IWHS) Cohort - Henry, Sarah A; Prizment, Anna E; Anderson, Kristin E (JOP. Journal of the Pancreas, 2013)
Context Studies have shown a relationship between history of diabetes and the risk of pancreatic cancer; however, the temporal relation between diabetes and pancreatic cancer is not clearly established. Objectives Diabetes and diabetes duration were examined in relation to pancreatic cancer in a population-based case-control study and prospective cohort. Methods Case-control study: pancreatic cancer cases (n=200) from the Midwest were frequency matched by age and sex to population controls (n=673). Logistic regression yielded odds ratios (ORs) and 95% confidence intervals (95% CI). Iowa Women’s Health Study (IWHS) cohort: 292 incident pancreatic cancer cases occurred between 1986-2008 among 36,084 post-menopausal, initially cancer-free women. Diabetes status and diagnosis age were ascertained at baseline and follow-ups. Proportional hazards regression yielded hazard ratios (HR, 95% CI) for pancreatic cancer in relation to baseline diabetes. Time-dependent analyses accounted for diabetes diagnosed after baseline. A nested-case control analysis assessed diabetes duration as a risk factor. Results In the case-control study, compared to participants without diabetes, the multivariate ORs (95% CI) for pancreatic cancer were 2.35 (1.24-4.47) for those with diabetes and 4.00 (0.94-16.9), 2.79 (0.97-8.04), and 2.40 (0.97-5.98) for diabetes durations of 2-5 years, 5.1-10 years, and more than 10 years, respectively. In IWHS, compared to no diabetes, multivariate-adjusted HRs for pancreatic cancer were 1.86 (1.23-2.83) for baseline diabetes and 1.94 (1.40-2.69) adding diabetes during follow-up. In an IWHS nested case-control analysis, ORs were 1.70 (0.78-3.67), 2.62 (1.48-4.65), and 2.10 (1.36-3.24) for diabetes durations of 2-5 years, 5.1-10 years and more than 10 years, respectively, versus no diabetes. Conclusions Diabetes is associated with pancreatic cancer risk and this is similar across different duration categories. Image: People (Division of Epidemiology and Community Health, University of Minnesota. Minneapolis, MN, USA).